Dasar-dasar penelitian kualitatif prosedur, teknik dan teori grounded Anselm Strauss, Juliet Corbin ; penyadur, H.M. Djunaidi Ghony ; penyunting, Muhammad Zakki - GHONY, H.M. Junaidi; Strauss, Anselm; Corbin, Juliet; Zakki, Muhammad (Bina Ilmu, 1997)
xii, 296 hlm. ; 23 cm